2010
DOI: 10.1152/ajplung.00147.2009
|View full text |Cite
|
Sign up to set email alerts
|

Molecular biological effects of selective neuronal nitric oxide synthase inhibition in ovine lung injury

Abstract: Neuronal nitric oxide synthase is critically involved in the pathogenesis of acute lung injury resulting from combined burn and smoke inhalation injury. We hypothesized that 7-nitroindazole, a selective neuronal nitric oxide synthase inhibitor, blocks central molecular mechanisms involved in the pathophysiology of this double-hit insult. Twenty-five adult ewes were surgically prepared and randomly allocated to 1) an uninjured, untreated sham group ( n = 7), 2) an injured control group with no treatment ( n = 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 58 publications
4
17
0
Order By: Relevance
“…PARP activates NF-B (9), which upregulates IL-8 and inducible NOS, setting into motion a positive-feedback loop. We have confirmed much of this hypothesis by blocking calcitonin gene-related peptide (17), different isoforms of NOS (5,24), PARP (25), and now RNS.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…PARP activates NF-B (9), which upregulates IL-8 and inducible NOS, setting into motion a positive-feedback loop. We have confirmed much of this hypothesis by blocking calcitonin gene-related peptide (17), different isoforms of NOS (5,24), PARP (25), and now RNS.…”
Section: Discussionsupporting
confidence: 55%
“…Combined burn and smoke inhalation injury in sheep closely reflects the pathophysiological changes in humans with these injuries (10), and previous studies with our model demonstrated that reactive nitrogen species (RNS) are critically involved in this process (5,24,28,36). We have also reported the presence of reactive oxygen species (ROS) in patients with burn and smoke inhalation injury (20).…”
supporting
confidence: 68%
See 1 more Smart Citation
“…13 The chosen dosage of 7-NI has been established in previous studies using the same and a similar animal model. 6,14,15 It has previously been demonstrated that infusion of 7-NI in sheep at a dose of 1 mg ⅐ kg Ϫ1 ⅐ h Ϫ1 effectively suppresses plasma nitrate/nitrite levels 6,14,15 and establishes plasma concentrations of 7-NI 15 far below the IC 50 reported for endothelial and inducible NOS. 16 All sheep were mechanically ventilated (Servo Ventilator 900C; Siemens, Elema, Sweden) with a tidal volume of 12-15 ml/kg and a positive-end expiratory pressure of 5 cm H 2 O during the entire study period of 24 h. The fraction of inspired oxygen was set at 1.0 for the first 3 h postinjury and was then adjusted to maintain sufficient oxygenation (arterial oxygen saturation more than 90%, partial arterial oxygen pressure 80 -100 mmHg) whenever possible.…”
Section: Experimental Protocolmentioning
confidence: 97%
“…Administration of 7-nitroindazole attenuated all of these responses, implicating neuronal nitric oxide synthase as having a key role in the pathology of inhalation injuries. 22 These studies offer the possibility of potential future therapies for the treatment of inhalation injuries.…”
Section: Inhalation Injurymentioning
confidence: 99%